2019
DOI: 10.15294/jdm.v10i1.18243
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Determinants of Individual Intention to Invest in Digital Risky Investment

Abstract: This study examines the effect of emotional intelligence, the locus of control, and risk aversion on intention to risky investment with financial literacy as moderating effect. This study uses 98 investors distributed by online questionnaire. Data examined using Partial Least Square (PLS) technique. The results show that the emotional intelligence, the locus of control have a positive effect and risk aversion and financial literacy have a negative effect on intention to a risky investment. However, there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
2
6
1
1
Order By: Relevance
“…Aydemir & Aren [37], for example, found a positive and significant relationship between locus of control and investment intention among several exchanges in Turkey. Abdillah et al [39] also found this positive and significant relationship in the Indonesia Stock Exchange. Research by Aydemir & Aren [37] shows that locus of control has a positive effect on investment intention.…”
Section: Locus Of Control and Investment Intentionmentioning
confidence: 69%
“…Aydemir & Aren [37], for example, found a positive and significant relationship between locus of control and investment intention among several exchanges in Turkey. Abdillah et al [39] also found this positive and significant relationship in the Indonesia Stock Exchange. Research by Aydemir & Aren [37] shows that locus of control has a positive effect on investment intention.…”
Section: Locus Of Control and Investment Intentionmentioning
confidence: 69%
“…First, there might be the presence of different variables that may impact the attitude of the investors due to differences in their financial and educational backgrounds. Therefore, in addition to the variables under study, there could also be certain other variables like perceived knowledge, perceived ease of use (Ichwan and Kasri, 2019), emotional intelligence, locus of control, risk aversion (Abdillah et al, 2019), profitability, convenience and anonymity (Yilmaz and Hazar, 2018), which may also impact the intention to invest in cryptocurrency. Therefore, future research can prioritize these factors impacting cryptocurrency investment decision after taking into account the investor preferences.…”
Section: Conclusion Limitations and Future Scopementioning
confidence: 99%
“…Informativeness is very important for potential investors in making decisions. The more information potential investors get, the more convincing they will be to take an action (Abdillah, Permatasari, & Hendrawaty, 2019). The social media used by the current millennial generation helps in gathering various information needed for potential investors.…”
Section: Discussionmentioning
confidence: 99%